Synthesis and Modeling of Temperature Distribution For Nanoparticles Produced Using Nd:YAG Lasers - Mu’ataz S. Hassan; Ziad A. Taha; Bassam G. Rasheed (Journal of Nanotechnology)
Nanosecond pulses of Nd:YAG laser were employed to produce silver and silicon nanoparticles by laser ablation process in liquid. Two Nd:YAG laser systems of 6 and 10 nanoseconds pulse duration with variable laser energy in the range 700–760 mJ were employed. Morphological investigation using AFM and TEM reveals the formation of silver and silicon nanoparticles with uniform size distribution. It is found that mean nanoparticles sizes of 50 and 70 nm for silver and silicon, respectively, are produced under similar laser parameters. Moreover, theoretical model was used to estimate the temperature distributions for both silver and silicon nanoparticles. It is also found that the maximum temperature of about 50 k K° and 70 k K° for silver and silicon nanoparticles, respectively, is generated when Nd:YAG of 10 ns is used to prepare nanoparticles. Zeta potential measurements reveal that silver nanoparticles are more stable than those of silicon prepared by similar conditions.